Desenvolvimento rural, trabalho cooperado e subjetividades: a trajetória de cooperação do Assentamento Sepé Tiaraju - Melo, Thainara Granero de (Universidade Federal de São Carlos, 2019)
This research investigates the relationship between rural development, cooperative work, and subjectivities. The field of analysis is the history of cooperation of a settled rural workers group. Firstly, I followed the implementation of Sustainable Rural Development Project (PDRS) Microbacias II. It was a public policy of the State of São Paulo which provided funds to Sepé Tiaraju rural settlement in the region of Ribeirão Preto. In a second moment, I recovered the previous experiences of cooperation of this group, aiming to understand how these experiences were articulated to implement the Microbacias programme. Considering cooperation as an organized social action to achieve common goals that is not limited to normative principles of formal arrangements, as well as an experience that requires thinking about individuals and subjectivities, I defined Social Psychology of Work as a theoretical perspective to conduct the study, from which a theoretical and conceptual framework was built combining concepts of Psychosociology and Institutional Bricolage. The hypothesis of the study is that unlike policymakers assume, a single policy or formal arrangement is insufficient to strengthen cooperation since the relationship between rural development, cooperation, and subjectivities is characterized by ambiguity, unpredictability, and processuality. The qualitative research and the case study were conducted in the Sepé Tiaraju Settlement through bibliographical and documentary research; participant observations recorded in field diaries; individual and collective semi-structured interviews with the settlers; discussion groups; and two activities of Reflexive Monitoring in Action (RMA) method - Timeline Workshops and Audiovisual Learning History - used as a strategy to return the research findings to the group. I applied the triangulation technique to articulate different sources of information, from which five categories were raised to analyze the trajectory of cooperation: institutions, organizations, powers, bounds, and identities. The study suggests that these categories and the three domains raised in the hypothesis underline a difficult type of cooperation between a deeply heterogeneous social group in interaction with different social agents and different prescribed cooperative arrangements. The experiences of cooperation were constructed by a complex articulation between bricolage processes – adaptations and contestations of formal arrangements - and less visible aspects of social relations, such as powers, emotions, and identities. These bricolage outcomes allowed the group to adjust the rules of cooperation unpredictably or creatively, as well as to reproduce unequal relationships. In this sense, cooperation is a complex process that cannot be prescribed by a single policy or intervention. Besides, it is necessary to discuss how supposedly cooperative arrangements displace the structural relations of inequality from the individuals' perspective. The research aims to contribute to clarifying which psychosocial processes are linked to work and daily life of these social groups inserted in Brazilian ruralities. Moreover, the theoretical framework may add to the recent debate of Psychology other interpretative categories about the dynamics of cooperation in rural areas.
Rural development, cooperative work and subjectivities: the history of cooperation of Sepé Tiaraju rural settlement
Keywords: Desenvolvimento rural; Trabalho cooperado; Subjetividades; Assentamento rural; Rural development; Cooperation; Subjectivities; Rural settlement; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL